2020
DOI: 10.3390/polym12051133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Mechanical Properties and Polymerization Kinetics of Polyamide-6 Composites

Abstract: This work reports the preparation of carbon fiber reinforced thermoplastic composites via the in situ anionic ring opening polymerization of ε-caprolactam. Vacuum assisted resin transfer molding was used to fabricate polyamide-6/carbon fiber composites at different molding temperatures. As a result, the higher polymerization of ε-caprolactam was observed with the condition at 140 °C for satisfactory impregnation. Regarding molding temperature, the physical properties of polyamide-6/carbon fiber were observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Overall, the sample molded at 140 °C had superior properties. The higher tensile and bending strengths of the sample molded at 140 • C indicate a relatively large degree of polymerization and crystallization at this temperature, as deduced from our previous study on the effect of temperature on the polymerization and crystallization of PA 6 [28]. Overall, the sample molded at 140 • C had superior properties.…”
Section: Mechanical Propertiessupporting
confidence: 60%
See 1 more Smart Citation
“…Overall, the sample molded at 140 °C had superior properties. The higher tensile and bending strengths of the sample molded at 140 • C indicate a relatively large degree of polymerization and crystallization at this temperature, as deduced from our previous study on the effect of temperature on the polymerization and crystallization of PA 6 [28]. Overall, the sample molded at 140 • C had superior properties.…”
Section: Mechanical Propertiessupporting
confidence: 60%
“…A 180 × 180 mm 2 sized rectangular mold and 1200 × 1700 mm 2 sized automotive part (hood) mold were considered for the mold filling process. From our previous research [28], the experimentally determined time-dependent viscosity of caprolactam was employed, and the critical processing time for ε-caprolactam was defined as 20 s. A numerical analysis was performed with four different temperature conditions: 140, 160, 180, and 200 • C, where a difference in the filling behavior with the processing time was expected based on the difference in the viscosity of the resin. The inlet pressure was set to 0.85 bar, and the outlet pressure was atmospheric pressure for all cases.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…PA6/CF composites manufactured via vacuum-assisted resin transfer molding (VARTM) were analyzed by Li et al [59] with different molding temperatures. As preliminary results, it is observed that the satisfactory temperature for impregnation of the material is 140ºC.…”
Section: Thermal Analyses Of Pa and The Influence Of Humiditymentioning
confidence: 99%
“…M.Xian et al, studied the effect of temperature on the mechanical properties and polymerization kinetics of polyamide-6 composites , from the experimental and modeling results, it can be concluded that the optimal temperature for polymerization is 140-160 •C, and the molding process must be finished within 20 second regardless of the shapes and sizes of the samples [22].…”
Section: Introductionmentioning
confidence: 99%